Symptoms affecting patient’s intake of food with lymphoma in outpatient chemotherapy - Andressa Madalozo Laffitte; Carolina Lane Alves Farias; Jessica Wszolek (O Mundo da Saúde)
Lymphomas are a malignant neoplasm which arises in the lymph nodes, which are involved in fighting infection. This cancer had the highest increase in incidence among oncohematological diseases. The objective of the study was evaluate the pos- sible gastrointestinal symptoms presented by the patient during treatment and relates them to food intake and nutritional status. The subjective global assessment was performed; body mass index, arm muscle area and assessed food intake, as well as presence of gastrointestinal symptoms in patients with lymphoma undergoing outpatient chemotherapy. The sample consisted of 30 patients of the Oncology Clinic Erasto Gaertner Hospital of Paraná service, between the months of May and June 2014, 33.3% with Hodgkin’s lymphoma and 66.7% with non-Hodgkin lymphoma. According to ASG 100% of patients were considered nourished, but 46.7% of patients had weight loss. According to the AMB, 57% of patients had some degree of malnutrition. In the BMI, 26.7% of adults were eutrophic, 30% were overweight, 13.3% were obese and none with malnutrition, in relation to the elderly 6.7% were underweight, 6.7% were eutrophic and 16.7 % overweight. There was a decrease in food intake by some patients after chemotherapy initiation, being nausea, dysgeusia, dry mouth and constipation the most frequent symptoms. Considering the gastrointestinal symptoms that interfere directly in the dietary pattern and weight loss caused by chemotherapy, the onco hematological patients should be considered at nutritional risk and receiving specialized nutritional monitoring to minimize its adverse side effects and improve their life quality.